2015
DOI: 10.1186/s12866-015-0348-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of IncF-type plasmids in multiresistant CTX-M-15-producing Enterobacteriaceae isolates from surgical-site infections in Bangui, Central African Republic

Abstract: BackgroundSurgical-site infection is the most frequent health care-associated infection in the developing world, with a strikingly higher prevalence than in developed countries We studied the prevalence of resistance to antibiotics in Enterobacteriaceae isolates from surgical-site infections collected in three major tertiary care centres in Bangui, Central African Republic. We also studied the genetic basis for antibiotic resistance and the genetic background of third-generation cephalosporin-resistant (3GC-R)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
(34 reference statements)
7
30
1
Order By: Relevance
“…As was already noted in studies from the Asian, European and the African continents which documented the emergence and spread of bla CTX-M-15 in humans and cattle (Madec et al, 2012; Zhang et al, 2013; Rafaï et al, 2015), CTX-M-15 was also found to be the predominant allele in this study. The gene was located on the chromosome or on different plasmids indicating extreme environmental mobility.…”
Section: Discussionsupporting
confidence: 89%
“…As was already noted in studies from the Asian, European and the African continents which documented the emergence and spread of bla CTX-M-15 in humans and cattle (Madec et al, 2012; Zhang et al, 2013; Rafaï et al, 2015), CTX-M-15 was also found to be the predominant allele in this study. The gene was located on the chromosome or on different plasmids indicating extreme environmental mobility.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of TEM, SHV and CTX-M genes alone in the study of Alibi et al in Tunisia was high compared to our results with 3.39% (4/118), 4.23% (5/118) and 11% (13/118) respectively [54]. In Mozambique, on 19 [57]. It is observed that the expression of bla CTX-M is currently more prevalent and as we report for the first time in Togo, more frequent in a triple combination with bla TEM and bla SHV .…”
Section: Discussioncontrasting
confidence: 67%
“…These plasmids have been largely reported in clinical isolates from humans around the world and more recently from cattle and pets in France, and from the fecal flora of healthy calves in the Netherlands (http://pubmlst.org/plasmid/) (Madec et al ., ; Dahmen et al ., ; Hordijk et al ., ). Their presence in different pathogen species and in different countries (Villa et al ., ; Dahmen et al ., ; Li et al ., ; Rafai et al ., ) suggests that horizontal transfer of plasmids rather than clonal dissemination is probably an important mechanism of bla CTX‐M‐15 spread.…”
Section: Resultsmentioning
confidence: 99%